Jude the obscure - Hardy, Thomas, 1840-1928. (United Kingdom : Transatlantic Press, 2012)
Hardy called'Jude the Obscure''a deadly war waged between flesh and spirit'. It is a tale of doomed love and unfulfilled promise that revolves around Jude Fawley, an ambitious and intelligent young man, his cousin Sue Bridehead and his academic mentor Phillotson.
Keywords: Prejudices -- Fiction; Social classes -- England -- Wessex -- Fiction; Stonemasons -- Fiction; Wessex (England) -- Social conditions -- Fiction